Kajian Produktivitas Instalasi Rangka Atap Baja Ringan: Studi Kasus di Bandung, Indonesia - Adrian Firdaus; Yohanes Lim Dwi Adianto; Zulkifli B. Sitompul; Antonius Trianto (Jurnal Ilmiah Rekayasa Sipil, 2020)
The needs of housing in Indonesia is increasing in conjunction with the population growth. This increment has to be addressed by an efficient construction process, which includes an adequate material and construction method selection. The utilization of light steel roof trusses is as an innovation which is considered better in terms of cost, time, and quality, com- pared to a conventional wood roof trusses. This research is aimed to identify the productivity of light steel roof trusses installation. The case study is a housing project in Bandung, which is compared to a historical data from several light steel roof subcontractors within Bandung area. The productivity from the direct observation on the case study is 9.821 m2/man-day, while the historical data processing generates 7.355 m2/man-day. This different is resulted from the ineffective working time. The ineffective working time covers worker’s break time, learning curve, and coordination time. Besides, this different could also be caused by the 7 hours’ assumption on the daily working hour. This assumption is not thoroughly achieved due to several factors which are weather and daily working efficiency. In conclusion the conservative value of the light roof steel trusses installation productivity is 7.355 m2/man-day.